Exploiting the Oral Microbiome to Prevent Tooth Decay: Has Evolution Already Provided the Best Tools? - Baker, Jonathon L.; Edlund, Anna (Frontiers in Microbiology, 2019)
To compete in the relatively exposed oral cavity, resident microbes must avoid being replaced by newcomers. This selective constraint, coupled with pressure on the host cultivate a beneficial microbiome, has rendered a commensal oral microbiota that displays colonization resistance, protecting the human host from invasive species, including pathogens. Rapid increases in carbohydrate consumption have disrupted the evolved homeostasis between the oral microbiota and dental health, reflected by the high prevalence of dental caries. Development of novel modalities to prevent caries has been the subject of a breadth of research. This minireview provides highlights of these endeavors and discusses the rationale and pitfalls behind the major avenues of approach. Despite efficacy, fluoride and other broad-spectrum interventions are unlikely to further reduce the incidence of dental caries. The most promising methodologies in development are those that exploit the exclusive nature of the healthy oral microbiome. Probiotics derived from the dental plaque of healthy individuals sharply antagonize cariogenic species, such as Streptococcus mutans. Meanwhile, targeted antimicrobials allow for the killing of specific pathogens, allowing reestablishment of a healthy microbiome, presumably with its protective effects. The oral microbiota manufactures a massive array of natural products, some of which are correlated with health, are likely to antagonize pathogens, and await further exploration. The prohibitive cost associated with sufficiently rigorous clinical trials, and the status of dental caries as a non-life-threatening condition will likely continue to impede the advancement of new therapeutics to market. Nevertheless, there is room for optimism, as it appears evolution may have already provided the best tools.